Narrative Nuances: Analyzing Speech Acts in Soman Chainani's 'The School for Good and Evil' Movie - Fitria Aprilia; Neisya Neisya; Whariyanti Whariyanti (VELES Voices of English Language Education Society, 2023)
This research analyzes the different types of speech acts in the movie "The School for Good and Evil" by Soman Chainani, as performed by seventeen distinct characters. While the film offers a captivating narrative, it also delves into instances where characters wrestle with understanding the deeper meanings of others' utterances. Employing a descriptive qualitative approach, this study meticulously examines the dialogues. Data collection techniques encompass a thorough examination of the movie script and an analysis of characters’ gestures. Findings highlight a diverse range of speech acts pivotal to the movie's storytelling. All forms of speech acts are evident, with a marked prominence of illocutionary acts such as ‘asking questions’ and ‘giving commands. Other examples include ‘giving directions’ and ‘representing information’. Notably, the identified perlocutionary acts are largely non-literal. The classification further underscores the consistent use of ‘directives’ and ‘representatives. The illocutionary acts in the movie cover a breadth of communicative functions, from querying, summoning, and instructing to expressing sentiments and stating positions.